Possible Role of Rickettsia fells in Acute Febrile Illness among Children in Gabon - (:unkn) unknown (My University, 2015)
Rickettsia felis has been reported to be a cause of fever in sub-Saharan Africa, but this association has been poorly evaluated in Gabon. We assessed the prevalence of this bacterium among children <15 years of age in 4 areas of Gabon; the locations were in urban, semiurban, and rural areas. DNA samples from 410 febrile children and 60 afe-brile children were analyzed by quantitative PCR. Overall, the prevalence of R. felis among febrile and afebrile children was 10.2% (42/410 children) and 3.3% (2/60 children), respectively. Prevalence differed among febrile children living in areas that are urban (Franceville, 1.3% [1/77]), semiur-ban (Koulamoutou, 2.1% [3/141]), and rural (Lastourville, 11.2% [15/134]; Fougamou, 39.7% [23/58]). Furthermore, in a rural area (Fougamou), R. felis was significantly more prevalent in febrile (39.7% [23/58]) than afebrile children (5.0% [1/20]). Additional studies are needed to better understand the pathogenic role of R. felis in this part of the world. O ver the past decade, reported cases of malaria and associated deaths have declined in Africa (1). This decrease has led to a search for other causes of fever in Africa, where unexplained febrile illnesses are one of the major health problems. In some sub-Saharan Africa countries, malaria treatments are still administered without a biolog-ic diagnosis. For example, an assessment of complicated malaria and other severe febrile illness cases in a pediatric ward in Libreville, Gabon, showed that 43.5% of the children who received an antimalarial treatment had micros-copy test results negative for malaria (2). Other studies have shown that, in addition to malaria, other bacterial infections are a major cause of fever in Africa (3–6). Staphylococcus aureus, Streptococcus pneumoniae, nontyphoidal Salmonella spp., Klebsiella pneumoniae, and Escherichia coli are the bacteria most often detected in sub-Saharan Africa by the culture method (7,8). The use of molecular tools
Keywords: African Research